Risk-sharing in the Pharmaceutical Industry The Case of Out-licensing - Reepmeyer, Gerrit. (Contributions to Management Science,, 2006)
The costs of developing a new drug have reached record levels in the pharmaceutical industry. As any failure of a new drug candidate can lead to significant losses, many pharmaceutical companies are looking for new approaches to reduce their exposure to R&D risks. In this context, the book deals with the topic of out-licensing as a novel form of risk-sharing collaborations. The phenomenon of out-licensing is illustrated by three major case studies of Novartis, Schering and Roche as well as several smaller case studies. In addition, the Noble Prize awarded economic theory of Adverse Selection is applied to analyze the topic theoretically. The gained insights allow identifying the critical parameters of out-licensing collaborations and thereby provide R&D managers with recommendations on how to conclude and manage this type of deals more effectively.